Effects of Fe2+ ion doping on LiMnPO4 nanomaterial for lithium ion batteries. Issue 32 (14th March 2016) - Xu, Han; Zong, Jun; Ding, Fei; Lu, Zhi-wei; Li, Wei; Liu, Xing-jiang
Abstract : Carbon-coating and Fe-doping of LiMnPO4 resulted in superior cycling and rate performance as LIB cathode materials. Abstract : To improve the electrochemical performance of LiMnPO4, a modified polyol reaction has been successfully developed for the preparation of LiMn x Fe1− x PO4 /C samples ( x = 0.2, 0.5, 0.8). The secondary particles of the acquired LiMn x Fe1− x PO4 /C samples are spherical or annular, and the primary particles are nano-sized (20–80 nm). The LiMn0.8 Fe0.2 PO4 /C has a higher energy density of 637 W h kg −1 compared with LiMn0.2 Fe0.8 PO4 /C (575 W h kg −1 ) and LiMn0.5 Fe0.5 PO4 /C (584 W h kg −1 ). The TEM image shows that the primary particles of LiMn0.8 Fe0.2 PO4 /C are uniformly covered by a 3 nm carbon layer, and it can deliver a high discharge capacity of 161 mA h g −1 at 0.05C. At a 0.5C discharge rate, the LiMn0.8 Fe0.2 PO4 /C can maintain 80.4% of its initial capacity after 900 cycles, and it also maintains 90% and 83% of its initial capacity at 45 °C and 55 °C respectively after 100 cycles. The results demonstrate that the modified polyol process is feasible for Fe-doping and carbon-coating to enhance the electrochemical performance of LiMnPO4 .